(untitled) (Indian Journal of Nematology, 2024)
Plant parasitic nematodes are the major hindrances in successful cultivation of commercial crops. Among different plant parasitic nematodes, Meloidogyne incognita is one of the world’s most widespread and devastating nematode pests. Utilization of native biocontrol agents is considered as one of the best practices for managing nematodes. Endophytic fungi have a significant role in managing plant parasitic nematodes following different mechanisms like parasitism, nematode paralysis, antibiosis, production of lytic enzymes, and competition for space. In the present study, efforts were made to isolate endophytic fungi from currant tomato plants (Solanum pimpinellifolium, commonly known as Kon Bilahi, grown mostly wild) in Assam. Fourteen fungal endophytes were isolated from shoot and root portions of tomato plants. The efficacy of the isolates was tested against second-stage juveniles (J2) of M. incognita, in vitro at three concentrations of 100, 50 and 25 per cent of culture filtrate (CF) and for four exposure times viz., 6, 12, 24 and 36 hrs. Isolate FETS10 was found to be the best, with 96.04 per cent juvenile mortality, followed by FETR3 and FETS11, with a mortality percentage of 77.44 and 66.24, respectively. Based on the result of the in vitro experiment, molecular characterization of the four best fungal endophytes was carried out by genomic DNA extraction and amplification of fungal ITS rDNA regions. These were identified as Aspergillus aculeatus (FETS10), Mortierella alpina (FETR3), Mucor racemosus (FETS11) and Fusarium oxysporum (FETR1). Dose-response models were used to determine the concentration of the potential fungal CF required to kill 50 per cent of M. incognita J2. LC50 values of the CFs of A. aculeatus, M. alpina, M. racemosus and F. oxysporum against M. incognita were 2.21, 15.31, 24.71 and 43.92 per cent, respectively, in 12 hrs exposure time.